Atypical Presentation of Cerebellopontine Angle Dermoid Cyst: A Case of Secondary Trigeminal Neuralgia - Prima Budi Prayogi; Galih Indra Permana; Hanis Setyono; Ferry Wijanarko; Geizar Arsika Ramadhana; Muhammad Fauzan Jauhari (Open Access Indonesian Journal of Medical Reviews, 2025)
Dermoid cysts are rare congenital ectodermal inclusion cysts, accounting for a small percentage of all intracranial tumors. Their occurrence in the cerebellopontine angle (CPA) is infrequent, and presentation as isolated trigeminal neuralgia (TN) is considered atypical. This study underscores that rare congenital lesions like dermoid cysts can manifest with relatively common neurological symptoms, prompting clinicians to consider a broader differential diagnosis A 60-year-old female presented with a two-year history of paroxysmal, shock-like pain in the left cheek and intraoral area, triggered by light touch, consistent with trigeminal neuralgia. Neurological examination was otherwise largely unremarkable initially, though the pain significantly impacted her quality of life and nutritional intake, leading to weight loss. Magnetic Resonance Imaging (MRI) revealed an extra-axial lesion in the CPA, compressing the trigeminal nerve. The lesion exhibited characteristics suggestive of an epidermoid or arachnoid cyst initially, but with features also compatible with a dermoid cyst. The patient underwent a retrosigmoid craniotomy for microsurgical excision of the lesion. Intraoperatively, a cystic lesion with contents suggestive of a dermoid cyst was found adherent to the trigeminal nerve and surrounding structures. Histopathological examination confirmed the diagnosis of a dermoid cyst. Postoperatively, the patient experienced significant relief from her trigeminal neuralgia. In conclusion, CPA dermoid cysts, though rare, should be considered in the differential diagnosis of secondary trigeminal neuralgia, even in atypical presentations. MRI is crucial for diagnosis, and surgical excision aiming for maximal safe resection is the mainstay of treatment, offering potential for symptom resolution. Long-term follow-up is necessary due to the potential for recurrence if the residual cyst wall remains. This case underscores the importance of considering rare pathologies in common clinical presentations.